Targeted therapies to treat Non-AIDS Defining Cancers in patients with HIV on HAART therapy – treatment considerations and research outlook - Deeken, John F. (2009)
PURPOSE OF REVIEW: Highly active antiretroviral therapy (HAART) has led to a dramatic improvement in the prognosis of patients diagnosed with HIV and AIDS. This includes a significant decline in the rates of AIDS-related cancers, including Kaposi Sarcoma and Non-Hodgkin's Lymphoma. Unfortunately, rates of Non-AIDS Defining Cancers (NADCs) are on the rise, and now exceed the rates of AIDS-related cancers in patients with HIV. Treating NADCs in patients who are on HAART therapy is an open and complicated clinical question. RECENT FINDINGS: Newer targeted therapies are now available to treat cancers which were historically refractory to traditional cytotoxic chemotherapy. HAART agents are notorious for causing drug-drug interactions. The co-administration of targeted chemotherapies with HAART could well impede the efficacy or increase the toxicity of these targeted therapies. Unfortunately little is known about possible drug-drug interactions because HIV patients are typically excluded from clinical trials. SUMMARY: We highlight what is known about how and why HAART agents can affect drug metabolism. We then present the clinical and pharmacological data for nine recently approved targeted therapies – imatinib, dasatinib, nilotinib, erlotinib, sunitinib, lapatinib, bortezomib, sorafenib, and temsirolimus. We conclude with considerations on how to use these new agents to treat NADCs, and discuss a future research agenda to better understand and predict potential HAART-targeted therapy interactions.